Pengaruh Media Video Promosi Kesehatan Terhadap Pengetahuan dan Sikap Remaja Dalam Keselamatan Berkendara di Kota Bandung - Herdhianta, Dhimas; Yulianti, Fenti; Assafa, Muhammad Rifqi (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2024)
Modern society put up his life with its high mobility. Its high mobility boosted the ever increasing traffic congestion. Road traffic accidents are the problems the longer compound to become more and more serious. The proportion of motorcycles in a traffic accident in west java province high with the percentage 70.5 % . The proportion of motorcycles in a traffic accident in west java province in the 15-24 age group of 73.49 % on 71.36 % junior high school of education. Safety riding it seeks drive where pay more attention to the safety of motorists and road users conducted to reduce accidents and as a result of traffic accidents. Research objectives it is analyzing the impact of media video promoting the health.Knowledge and attitudes of young people in the city of bandung drive in safety. The results is showed that there was an increase in knowledge after the intervention with a percentage of 6.65%, there was an increase in positive attitudes after the intervention with a percentage of 19.58%. The p value of knowledge and attitude before and after the intervention was p=0.000 (p<0.5). The conclusion of this study is that there is an effect of health promotion video media on adolescents' knowledge and attitudes about driving safety in Bandung City.